Coping with a nuclearizing Iran - Dobbins, James, 1942- (Rand Corporation monograph series, 2011)
It is not inevitable that Iran will acquire nuclear weapons or even that it will gain the capacity to quickly produce them. U.S. and even Israeli analysts continually push their estimates for such an event further into the future. Nevertheless, absent a change in Iranian policy, it is reasonable to assume that, some time in the coming decade, Iran will acquire such a capability. Most recent scholarly studies have also focused on how to prevent Iran from acquiring nuclear weapons. Other, less voluminous writing looks at what to do after Iran becomes a nuclear power. What has so far been lacking is a policy framework for dealing with Iran before, after, and, indeed, during its crossing of the nuclear threshold. This monograph attempts to fill that gap by providing a midterm strategy for dealing with Iran that neither begins nor ends at the point at which Tehran acquires a nuclear weapon capability. It proposes an approach that neither acquiesces to a nuclear-armed Iran nor refuses to admit the possibility -- indeed, the likelihood -- of this occurring.